Teknologi dalam Penerimaan Peserta Didik Baru: Akomodasi dan Tantangan Kultural - Hamdan, Hamdan; Aprina, Astia; Rochman, Maman; Mulyadi, Lintang; Subasman, Iman; Prihadi, Yucki; Widiantari, Dian (Fakultas Agama Islam Universitas Muhammadiyah Bandung, 2024)
The nationally implemented zoning system encourages schools, including private schools, to develop more effective and efficient enrollment methods. SDIT RMK Kuningan adopted Linktree to facilitate access to information and registration of new students online. This research uses the case study method with data collection techniques through observation, interviews, and documentation. Data analysis is carried out by triangulation method to ensure the validity of the results. The results showed that although the implementation of Linktree on PPDB at SDIT RMK Kuningan provides easy access to information and registration, this platform has not been able to significantly increase the quantity of new students. Some of the factors that influence this result are ineffective marketing, competition with other schools, suboptimal content and quality of information, school programs and facilities that are still in the development stage, and socio-cultural conditions of the community that are not fully ready for the adoption of online registration systems. Theimportance of a strong marketing strategy, delivery of quality information, and a deep understanding of the socio-cultural conditions of the community in the implementation of educational technology. Keywords: Linktree; Education Marketing; Elementary School; Educational Technology.